2020
DOI: 10.1007/s11011-020-00617-z
|View full text |Cite
|
Sign up to set email alerts
|

One drug to treat many diseases: unlocking the economic trap of rare diseases

Abstract: There are two major problems with the development of therapies for rare diseases. First, among over 7000 such diseases, the vast majority are caused by genetic defects and/or include neurodegeneration, making them very difficult to treat. Second, drugs for rare diseases, so-called orphan drugs, are extremely expensive, as only a small number of patients are interested in purchasing them. This results in the appearance of a specific economic trap of rare diseases; namely, despite high biomedical, pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Historically, due to the small prevalence of individual RDs, and the heterogeneity in disease etiology, clinical presentation, healthcare needs, and cost implications across difference RDs, rare diseases were viewed as diseases that may be individually debilitating but with limited public health implications. Advances in science and research have now shown several commonalities across RDs: first, many RDs share the same genetic or environmental risk factors [ 2 ]; second, there is evidence that therapeutic approaches that work for multiple RDs are both feasible and cost-effective [ 10 ]; third, patients with different RDs often share similar clinical experiences and care journeys. For instance, the phenomenon often regarded as the extensive “diagnostic odyssey” is known to affect many RD communities and results in significant delay in appropriate treatment, emotional stress, and economic loss [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, due to the small prevalence of individual RDs, and the heterogeneity in disease etiology, clinical presentation, healthcare needs, and cost implications across difference RDs, rare diseases were viewed as diseases that may be individually debilitating but with limited public health implications. Advances in science and research have now shown several commonalities across RDs: first, many RDs share the same genetic or environmental risk factors [ 2 ]; second, there is evidence that therapeutic approaches that work for multiple RDs are both feasible and cost-effective [ 10 ]; third, patients with different RDs often share similar clinical experiences and care journeys. For instance, the phenomenon often regarded as the extensive “diagnostic odyssey” is known to affect many RD communities and results in significant delay in appropriate treatment, emotional stress, and economic loss [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On average therefore, each remedy was suggested to treat over 15 ailments. Though the “one drug for many diseases” approach may not only reduce the cost of treatment of multiple infections 41 , it can also increase the number of individuals (suffering from different ailments) who may consume the same drug, and hence get exposed to its associated risks such as pathogenic microbial contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a significant proportion of these patients do not respond to available therapies because of partial or complete loss of response (LOR). This results in the emergence of an economic trap of rare diseases; specifically, despite the high biomedical, pharmaceutical, and technological potential, the development of new drugs is blocked by the economic reality and lack of effectiveness of the drugs [10].…”
Section: Current Problems In Diagnosis Therapy and Follow-up Of Patie...mentioning
confidence: 99%